2010
DOI: 10.3141/2145-07
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Proportional Fitting Procedure to Determine Bus Route Passenger Origin–Destination Flows

Abstract: The advent of automatic passenger counter (APC) technologies is resulting in the collection of comprehensive boarding and alighting data on an ongoing basis across transit networks. The availability of APC data offers a new opportunity to determine origin–destination (O-D) flows on a frequent and comprehensive basis. In this paper, the performance of a simple procedure for route-level O-D flow determination requiring only boarding and alighting data is investigated. Specifically, the performance of the iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…When a priori information is not available, a null base matrix, which assigns the same value (e.g., one) to all feasible OD pairs and zeroes to all infeasible OD pairs, can be used. Empirical studies have shown that the IPF method produces reasonably good OD flow estimates ] and that the IPF estimates are similar to those produced by some other methods .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…When a priori information is not available, a null base matrix, which assigns the same value (e.g., one) to all feasible OD pairs and zeroes to all infeasible OD pairs, can be used. Empirical studies have shown that the IPF method produces reasonably good OD flow estimates ] and that the IPF estimates are similar to those produced by some other methods .…”
Section: Introductionmentioning
confidence: 67%
“…By doing so, the origin and destination stops of this passenger are identified. Eventually, OD flow information was collected from 2,244 passengers .…”
Section: Numerical Evaluation On An Operational Bus Routementioning
confidence: 99%
“…To this end, the IPF procedure generates a sequence of matrices (A(t)), called the IPF sequence, by alternately fitting rows and columns to match their respective marginals. The procedure is in use in many disciplines for problems such as calculating maximum likelihood estimators in graphical log-affine models (Lauritzen, 1996, Chapter 4.3.1), ranking webpages (Knight, 2008), determining passenger flows (McCord et al, 2010) or calculating seats in parliaments (Pukelsheim, 2014b, Chapter 14).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the IPF procedure generates a sequence of matrices, called the IPF sequence, by alternately fitting rows and columns to match their respective marginals. The procedure is in use in many disciplines for problems such as calculating maximum likelihood estimators in graphical log-affine models (Lauritzen [13,Chapter 4.3.1]), ranking webpages (Knight [11]) or determining passenger flows (McCord et al [15]). …”
Section: Introductionmentioning
confidence: 99%